2013
DOI: 10.4028/www.scientific.net/amm.357-360.1124
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Performance of Polycarboxylate Superplasticizers with Hydrophobic Side Chains

Abstract: Based on polycarboxylate chemistry, polycarboxylate superplasticizers (PCs) with hydrophobic side chains were synthesized through radical copolymerization reaction. The molecular weight and polydispersity index were analyzed by gel permeation chromatograph (GPC), and the results showed the same structural information. The performances of PCs in cement paste were tested by measuring the fluidity and fluidity retention. The slump and the compressive strengths of concrete were also determined. Additionally, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Similar to the impact of mixing on the silicate phases, it is likely that the increased mixing intensity will also impact the formation of hydrates precipitating from the aluminate phases. Ettringite has a considerable impact on the rheological behavior and stiffening of fresh cement pastes [40,48] within the paste matrix and air will also affect rheological properties [51,52]. Thus, the greater sensitivity to mixing intensity seen in the plasticized mixtures as compared to the non-plasticized mixtures could be due to the polycarboxylate-based admixture inducing changes within the paste that modified the fundamental rheological response of the paste systems.…”
Section: Changes In the Chemical Environment Of Cement Pastementioning
confidence: 99%
“…Similar to the impact of mixing on the silicate phases, it is likely that the increased mixing intensity will also impact the formation of hydrates precipitating from the aluminate phases. Ettringite has a considerable impact on the rheological behavior and stiffening of fresh cement pastes [40,48] within the paste matrix and air will also affect rheological properties [51,52]. Thus, the greater sensitivity to mixing intensity seen in the plasticized mixtures as compared to the non-plasticized mixtures could be due to the polycarboxylate-based admixture inducing changes within the paste that modified the fundamental rheological response of the paste systems.…”
Section: Changes In the Chemical Environment Of Cement Pastementioning
confidence: 99%
“…e results showed that fractions of higher molar weight were adsorbed to a larger extent than fractions of lower molecular weight. Yang [36] used azobisisobutylamidine hydrochloride (AIBA•2HCl) as initiator in polymerization of polyoxyethylene allyl ether (APEG) and maleic anhydride (MA) to synthesize PCE-1. Also, Isoamyl enol polyoxyethylene ether (TPEG), the activity of acrylic acid (AA) and methacrylic sulfonate (MAS) was used to synthesize PCE-2.…”
Section: Direct Polymerizationmentioning
confidence: 99%